Pure mathematics 1 - Emanuel, Rosemary (Advanced mathematics, 2001)
Providing your students with a thorough understanding of AS and A2 Pure Mathematics. * Includes detailed worked examples, a wealth of practice, revision and examination exercises. * Book 1 provides bridging material from GCSE with plenty of background algebra. Book 2 contains Advanced Extension material to stretch more able students and prepare them for the Advanced Extension Awards. * Each chapter contains a range of graded exercises to build students' knowledge and confidence and consolidate students' learning. * Regular revision exercises, Key points, Test yourself exercises and exam questions provide complete practice for AS and A2.